A bibliometric review of energy justice literature - Ferrall-Wolf, Isa; Gill-Wiehl, Annelise; Kammen, Daniel M. (Frontiers in Sustainable Energy Policy, 2023)
Introduction Academic literature on energy justice sits at the intersection of a complex ecosystem of technologies, geographies, disciplinary traditions, terminologies, frameworks, theories, and methods. Its recent and rapid growth suggests it is of interest to a large number of stakeholders. However, these same features make aggregation and summarization a considerable undertaking. Methods This article uses advanced bibliometric analytics to synthesize this disparate and varied metadata to characterize trends in the treatment of energy justice in academic literature. The review covers 4,196 articles published between 1983 and 2023 with methods appropriate to the number and diversity of publications and associated subfields. Results We document distinct uses of similar terminologies across subfields in literature, inequitable ratios of global research compared to absolute levels of energy poverty, and the large but under-recognized contribution of cooking to the energy justice literature. Discussion In summarizing this voluminous literature and analyzing thematic changes over time, we provide scaffolding for more detailed reviews to place themselves within the larger interconnected literature network.